PERSONAL CHARACTERISTICS IN CHILDREN'S PSYCHOLOGY AS AN OBJECT OF RESEARCH - Nargiza A. Askarova; Tolib R. Bekmirov; Khabiba B. Nurbaeva; Nasiba B. Muminova; Alpamis B. Amangeldiev (The Bioscan, 2024)
This article analyzes the peculiarities of mental states in children. The conducted methods are mainly aimed at the study and analysis of neurotic conditions in mothers and their children and are part of our scientific research.